The development of speechreading skills in Chinese students with hearing impairment - Zhang, Fen; Lei, Jianghua; Gong, Huina; Wu, Hui; Chen, Liang (Frontiers in Psychology, 2022)
The developmental trajectory of speechreading skills is poorly understood, and existing research has revealed rather inconsistent results. In this study, 209 Chinese students with hearing impairment between 7 and 20 years old were asked to complete the Chinese Speechreading Test targeting three linguistics levels (i.e., words, phrases, and sentences). Both response time and accuracy data were collected and analyzed. Results revealed (i) no developmental change in speechreading accuracy between ages 7 and 14 after which the accuracy rate either stagnates or drops; (ii) no significant developmental pattern in speed of speechreading across all ages. Results also showed that across all age groups, speechreading accuracy was higher for phrases than words and sentences, and overall levels of speechreading speed fell for phrases, words, and sentences. These findings suggest that the development of speechreading in Chinese is not a continuous, linear process.